2018
DOI: 10.1534/genetics.118.301685
|View full text |Cite
|
Sign up to set email alerts
|

Directional Selection Rather Than Functional Constraints Can Shape the G Matrix in Rapidly Adapting Asexuals

Abstract: Genetic covariances represent a combination of pleiotropy and linkage disequilibrium, shaped by the population's history. Observed genetic covariance is most often interpreted in pleiotropic terms. In particular, functional constraints restricting which phenotypes are physically possible can lead to a stable G matrix with high genetic variance in fitness-associated traits, and high pleiotropic negative covariance along the phenotypic curve of constraint. In contrast, population genetic models of relative fitne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…We therefore also simulate the simultaneous evolution of two traits (k = 1, 2), with beneficial mutations of fitness effect s k appearing at rate U k , using an exten-220 sion of the method of Gomez et al [26]. We consider strong selection relative to population size, such that 1/N s k ≤ 1.…”
Section: (D) Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore also simulate the simultaneous evolution of two traits (k = 1, 2), with beneficial mutations of fitness effect s k appearing at rate U k , using an exten-220 sion of the method of Gomez et al [26]. We consider strong selection relative to population size, such that 1/N s k ≤ 1.…”
Section: (D) Simulationsmentioning
confidence: 99%
“…In the last step we set 245 abundances of deterministic classes (n * i,j > 1/Q i,j ) to n i,j (t + 1) = Round n * i,j (t) , while classes that grow stochastically (n * i,j ≤ 10/Q i,j ) are instead sampled from a Poisson distribution with mean n * i,j (t). We implemented the simulation method described 250 above using Matlab code originally developed by Pearce and Fisher [32], modified by Gomez et al [26] to deal with two traits, and here modified to allow those traits to have distinct mutation rates and selection coefficients.…”
Section: (D) Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore need a quantitative description of both between-population as well as within-population covariation of traits of microbial populations in this regime. In the present study, we focus on between-population covariation in growth traits, but recent work by Gomez et al (2019) provides insight into the case of within-population covariation. They showed that a tradeoff across individuals within a population evolves between two quantitative traits under positive, additive selection; this suggests that while growth rate and lag time will be negatively correlated across populations ( Figure 5, D and E), they should be positively correlated within populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Robertson (1961) model presupposes sequential, complete sweeps due to directional selection on initially rare QTL alleles, which may not be case when alleles are maintained at intermediate frequencies under stabilizing selection, as recently suggested with Drosophila experiments (Barghi et al, 2019) and likely to be the case here (Chelo and Teotónio, 2013). It is also possible, and perhaps probable in our setting, that small allele frequency and LD differences between replicate populations due to sampling of the domesticated population were accentuated by selection during the focal stage, resulting in variation between replicate populations of QTL effects on trait covariances (Bohren et al, 1966; Gomez et al, 2019). This process should be dampened by linked selection (Hill and Robertson, 1966; Zhang and Hill, 2005), although strong oligogenic sign epistasis we observed previously for fitness-related traits may exacerbate such sampling effects (Noble et al, 2017).…”
Section: Discussionmentioning
confidence: 99%